The El Horror uranium anomaly in northeastern Sonora, Mexico: Constraints from geochemical and mineralogical approaches. (December 2017) - Grijalva-Rodríguez, T.; Valencia-Moreno, M.; Calmus, T.; Del Rio-Salas, R.; Balcázar-García, M.
Abstract: This work reviews the characteristics of the El Horror uranium prospect in northeastern Sonora, Mexico. It was formerly detected by a radiometric anomaly after airborne gamma ray exploration carried out in the 70's by the Mexican government. As a promising site to contain important uranium resources, the El Horror was re-evaluated by CFE (Federal Electricity Commission) by in situ gamma ray surveys. The study also incorporates rock and stream sediment ICP-MS geochemistry, X-ray diffraction, X-ray fluorescence, Raman spectrometry and Scanning Electron Microscopy (SEM) to provide a better understanding of the radiometric anomaly. The results show that, instead of a single anomaly, it comprises at least five individual anomalies hosted in hydrothermally altered Laramide (80-40 Ma) andesitic volcanic rocks of the Tarahumara Formation. Concentrations for elemental uranium and uranium calculated from gamma ray surveys (i.e., equivalent uranium) are not spatially coincident within the anomaly, but, at least at some degree, they do so in specific sites. X-ray diffraction and Raman spectrometry revealed the presence of rutile/anatase, uvite, bukouvskyte and allanite as the more likely mineral phases to contain uranium. SEM studies revealed a process of iron-rich concretion formation, suggesting that uranium was initially incorporated to the system by adsorption, but was largely removed later during incorporation of Fe +3 ions. Stream sediment geochemistry reveals that the highest uranium concentrations are derived from the southern part of the Sierra La Madera batholith (∼63 Ma), and decrease toward the El Horror anomaly. Graphical abstract: A primary source of uranium from a magmatic/hydrothermal system associated with a ∼60 Ma pluton (SLM) is partly displaced by a Miocene high-angle normal fault, in a block roofed by comagmatic volcanic rocks (TF). Stream sediments coming from the SLM to the El Horror prospect (EH) allocate the higher U values found. Miocene basin-fill clastic sediments (BF) may be covering part of the mineralized system. Highlights: This study indicates that equivalent and elemental uranium are not consistent. The radiometric anomaly shows four peaks of uranium on ∼60 Ma old volcanic rocks. U was incorporated by adsorption and then removed by incorporation of Fe +3 ions. U in stream sediments points out the Sierra La Madera batholith as a likely source.